LEGAL ASPECTS OF HEALING THERAPY PROGRAM METHADON (PTRM) TO HEALTH PERSONNEL AND PATIENTS AT THE REGIONAL HOSPITAL DR. DJASAMEN SARAGIH PEMATANG SIANTAR CITY - Mulyadi Mulyadi; Elvira Fitriyani Pakpahan; Ferry Duan (Magister Kenotariatan Universitas Pasundan, 2021)
Drugs (narcotics, psychotropics, and dangerous drugs) have basically been used by mankind for a long time. Many types of narcotics and psychotropics provide great benefits when used properly and correctly. In the field of medicine, narcotics and psychotropic substances can cure various diseases and end suffering. This indicates, drugs do not always have a bad impact. The problem arises when drugs are abused and used excessively. The problem of drug use disorders (narcotics, psychotropics and other addictive substances) is a complex problem whose management involves many scientific fields, both medical and non-medical. Drug use disorders are very complex bio-psycho-socio-cultural problems that need to be addressed in a multidisciplinary and cross-sectoral manner in a comprehensive and consistent program. This is in accordance with the provisions of Law Number 35 of 2009 concerning narcotics in article 54. Djasamen Saragih Regional General Hospital Pematang Siantar City is one of the hospitals that participate in carrying out medical rehabilitation and social rehabilitation through the Methadon Maintenance Therapy Program (PTRM).In this case, from the applicable law, the MMT program is adequate although it needs improvements both in the ability of health workers, both patient non-compliance in undergoing the program and the participation of local governments in supporting the improvement of the ability of health workers in the MMT program and the need for implementing this program with spiritual therapy.